The RNA N6‐methyladenosine modulator HNRNPA2B1 is involved in the development of non‐small cell lung cancer. (14th November 2021) - Jin, Luming; Chen, Chaoyang; Yao, Jianyu; Yu, Zhichen; Bu, Liang
Abstract: The key N 6 methyladenosine (m 6 A) RNA methylation regulator is associated with multiple tumour progression. However, the m 6 A‐associated regulators that influence non‐small cell lung cancer (NSCLC) development have not been fully clarified. The m 6 A regulator expression pattern of NSCLC patients from The Cancer Genome Atlas (TCGA) dataset was identified. Aberrations of m6A modulators are related to NSCLC development via cBioPortal database. Furthermore, we found that IGF2BP2, IGF2BP3, HNRNPA2B1, and FTO are significantly correlated with advanced stage disease or clinical outcomes in NSCLC by UALCAN and Kaplan–Meier plot. Bioinformatics analysis showed that m 6 A modulators (IGF2BP2, IGF2BP3, HNRNPA2B1, and FTO) are associated with immunomodulator and immune infiltration expression in NSCLC via the Tumor Immune Estimation Resource (TIMER) database. The co‐expression between these m6A‐associated modulators was analysed by protein‐protein interaction networks. Finally, we found that HNRNPA2B1 promotes NSCLC development in vitro by regulating cell proliferation and metastasis functions via Cell Counting Kit 8 (CCK8) and transwell assay. Our study showed that HNRNPA2B1 is a promising target and biomarker for cancer therapy in NSCLC.